2012
DOI: 10.1002/rcm.6288
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolic investigation of moxifloxacin using liquid chromatography/electrospray ionization tandem mass spectrometry in combination with online hydrogen/deuterium exchange experiments

Abstract: RATIONALE Tuberculosis is a leading cause of death from an infectious disease and moxifloxacin is an effective drug as compared to other fluoroquinolones. To date only two metabolites of the drug are known. Therefore, the present study on characterization of hitherto unknown in vivo metabolites of moxifloxacin using liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI‐MS/MS) is undertaken. METHODS In vivo metabolites of moxifloxacin have been identified and characterized by using LC/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…However, the relative abundances of the product ions resulting from the same fragmentation patterns varied greatly. Raju et al (2012) reported several characteristic ions formed by cleavage of the benzene ring, whereas negligible amounts of these products were observed in this analysis. Many abundant radical ions resulting from loss of CH 3 or CH 3 O were detected in this work, although Raju et al (2012) observed small numbers of these ions.…”
mentioning
confidence: 50%
See 3 more Smart Citations
“…However, the relative abundances of the product ions resulting from the same fragmentation patterns varied greatly. Raju et al (2012) reported several characteristic ions formed by cleavage of the benzene ring, whereas negligible amounts of these products were observed in this analysis. Many abundant radical ions resulting from loss of CH 3 or CH 3 O were detected in this work, although Raju et al (2012) observed small numbers of these ions.…”
mentioning
confidence: 50%
“…Raju et al (2012) reported several characteristic ions formed by cleavage of the benzene ring, whereas negligible amounts of these products were observed in this analysis. Many abundant radical ions resulting from loss of CH 3 or CH 3 O were detected in this work, although Raju et al (2012) observed small numbers of these ions. Although the structures of moxifloxacin and analog 1 are similar, the relative abundances of products from the same fragmentation patterns varied greatly ( Figure 2 and Table 2).…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…These metabolism studies are generally carried out by employing in vitro and in vivo systems [8] followed by using modern analytical techniques. Liquid chromatography-mass spectrometry (LC-MS) is the most popular and versatile analytical technique which has been widely used for the identification of trace levels of drugs and their metabolites in various biological matrices due to its high sensitivity [9][10][11][12]. Several strategies, such as MS/MS, MS n , on-line hydrogen/ deuterium exchange experiments, accurate mass measurements, softwares dedicated to the metabolite prediction (in silico tools), chemical derivatization and radio-labeling of parent drugs were used for structural characterization of metabolites [9][10][11][12][13][14][15].…”
Section: Editorialmentioning
confidence: 99%